Banalidade do Mal: colapsos morais no 3º Reich - VAZ, éden Farias (2011)
This work explores the meaning of the expression Banality of Evil, coined by Hannah Arendt in her investigation about Adolf Eichmann in Jerusalem. It intends to question its meaning to the logistics of extermination in the Holocaust. Investigates on the one hand, aspects of a moral collapse about our common understandings about the problem of evil, and by the other, the context of bureaucracy that propitiated the novelty of this new form of evil by its singular lack of roots as well as political and moral implications in relation to individual responsibility. Through the conceptual analysis of the problem of evil, along with a series of mismatches in the reasons for doing evil, we propose an interpretation of the meaning of the Banality of Evil.